Diverse expression patterns of the EMT suppressor grainyhead‐like 2 (GRHL2) in normal and tumour tissues. Issue 4 (25th September 2015) - Riethdorf, Sabine; Frey, Sabrina; Santjer, Sonja; Stoupiec, Malgorzata; Otto, Benjamin; Riethdorf, Lutz; Koop, Christina; Wilczak, Waldemar; Simon, Ronald; Sauter, Guido; Pantel, Klaus; Assmann, Volker
Abstract : The transcription factor grainyhead‐like 2 (GRHL2) plays a crucial role in various developmental processes. Although GRHL2 recently has attracted considerable interest in that it could be identified as a novel suppressor of the epithelial‐to‐mesenchymal transition, evidence is emerging that GRHL2 also exhibits tumour‐promoting activities. Aim of the present study therefore was to help defining the relevance of GRHL2 for human cancers by performing a comprehensive immunohistochemical analysis of GRHL2 expression in normal ( n = 608) and ( n = 3, 143) tumour tissues using tissue microarrays. Consistent with its accepted role in epithelial morphogenesis, GRHL2 expression preferentially but not exclusively was observed in epithelial cells. Regenerative and proliferating epithelial cells with stem cell features showed a strong GRHL2 expression. Highly complex GRHL2 expression patterns indicative of both reduced and elevated GRHL2 expression in tumours, possibly reflecting potential tumour‐suppressing as well as oncogenic functions of GRHL2 in distinct human tumours, were observed. A dysregulation of GRHL2 expression for the first time was found in tumours of non‐epithelial origin ( e.g ., astrocytomas, melanomas). We also report GRHL2 copy number gains which, however, did not necessarily translate into increased GRHL2 expression levels in cancer cells. Results obtained by meta‐analysis of gene expression microarray data in conjunction with functional assays demonstrating a direct regulation of HER3 expression further point to a potential therapeutic relevance of GRHL2 in ovarian cancer. Hopefully, the results presented in this study may pave the way for a better understanding of the yet largely unknown function of GRHL2 in the initiation, progression and also therapy of cancers. Abstract : What's new? Transcription factor "grainyhead‐like 2" (GRHL2) acts as a tumour suppressor in breast cancer, but it may have tumour‐promoting activities in other cancers. In this study using immunohistochemistry and tissue microarrays, the authors found that GRHL2 expression is dysregulated in a broad range of malignant tumours, including astrocytoma, melanoma, breast and ovarian cancers. These results indicate that GRHL2 may offer a potential therapeutic target, and further studies should enhance our understanding of its role in numerous types of cancer.